The predictor of non-suicidal self-injury behavior among adolescents: a cross-sectional study - Iswanti, Dwi Indah; Lai, Lee-Lee; Saifudin, I Made Moh. Yanuar; Kandar, Kandar; Dewi, Rian Kusuma; Cahyaningrum, Dessy Dwi (Universitas Airlangga, 2024)
Introduction: Non-Suicidal Self-Injury (NSSI) among adolescents is a prevalent issue in Indonesia. Comprehensive understanding of NSSI is essential for uncovering the factors that trigger and predispose adolescents to such behavior. This knowledge serves as a foundation for crafting targeted nursing interventions to address and mitigate NSSI among this vulnerable population. This study aimed to identify determinant factors contributing to the occurrence of Non-Suicidal Self-Injury behavior in adolescents. Methods: The study employed a cross-sectional approach conducted between October and December 2023, with 570 respondents selected through simple random sampling. Socio-demographic, precipitating, and predisposing factors were measured using a checklist sheet. The Self-Harm Inventory (SHI) instrument was utilized to assess NSSI. Data analysis involved Pearson correlation and multiple regression to examine the relationships between variables. Results: The study revealed significant relationships among five variables. Gender (p-value = 0.004), bullying (p-value = 0.002), disappointment (p-value = 0.001), sharing place (p-value = 0.002), and communication pattern (p-value = 0.010) were identified as factors associated with Non-Suicidal Self-Injury behavior in adolescents. On the other hand, personality (p-value = 0.174), environment (p-value = 0.260), coping mechanism (p-value = 0.458), and parenting style (p-value = 0.054) showed no association with Non-Suicidal Self-Injury behavior. Conclusions: The findings underscore the significance of disappointment and the absence of a supportive environment in influencing NSSI. This highlights important considerations for healthcare professionals, educators, and policymakers. Strategies should encompass comprehensive approaches, early detection, and targeted interventions to foster supportive environments and address the complex nature of NSSI among adolescents.